PENINGKATAN AKTIVITAS SISWA DALAM PEMBELAJARAN PKN MENGGUNAKAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER - Ashari, Wahyu Ningtyas; Sabri, Tahmid; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to obtain information and describes the increased activity of students using the cooperative learning model type Numbered Heads Together in teaching civic education in grade III SDN 29 Pontianak North.The research method used is descriptive method with classroom action research (PTK). The study subjects is 30 student.Data collection techniques with a data collector that is the assessment sheet learning ability of teachers to plan, implement learning,and the sheet on student learning activities. This research was done 3 cycles,the results showed that (1) On the ability of teachers plan learning in the first cycle (average 2,78) second meeting (average 3,02), third meeting (average 3,33). (2) On the ability of teachers to implement the first meeting of the learning cycle (average 2,78), second meeting (average 3,15), third meeting (average 3,43). (3) The first cyle student learning activities (average 32,49%) second cycle (average 45,83%), third cyle (average 61,66%). Keywords: Students Activity, Civic Education, Cooperative Learning, Numbered Head Together Type